Successful Recritment And Selection: A practical guide for line managers/The Art of HRD, Sukses merekrut dan menyeleksi karyawan panduan praktis bagi manajer - DALE, Margaret (PT. Bhuana Ilmu Populer, 2003)
Successful Recruitment And Selection: A practical guide for line managers.